Microfocusing at the PG1 beamline at FLASH. (1st January 2016) - Dziarzhytski, Siarhei; Gerasimova, Natalia; Goderich, Rene; Mey, Tobias; Reininger, Ruben; Rübhausen, Michael; Siewert, Frank; Weigelt, Holger; Brenner, Günter
Abstract : The Kirkpatrick–Baez (KB) refocusing mirror system installed at the PG1 branch of the plane‐grating monochromator beamline at the soft X‐ray/XUV free‐electron laser in Hamburg (FLASH) is designed to provide tight aberration‐free focusing down to 4 µm × 6 µm full width at half‐maximum (FWHM) on the sample. Such a focal spot size is mandatory to achieve ultimate resolution and to guarantee best performance of the vacuum‐ultraviolet (VUV) off‐axis parabolic double‐monochromator Raman spectrometer permanently installed at the PG1 beamline as an experimental end‐station. The vertical beam size on the sample of the Raman spectrometer, which operates without entrance slit, defines and limits the energy resolution of the instrument which has an unprecedented design value of 2 meV for photon energies below 70 eV and about 15 meV for higher energies up to 200 eV. In order to reach the designed focal spot size of 4 µm FWHM (vertically) and to hold the highest spectrometer resolution, special fully motorized in‐vacuum manipulators for the KB mirror holders have been developed and the optics have been aligned employing wavefront‐sensing techniques as well as ablative imprints analysis. Aberrations like astigmatism were minimized. In this article the design and layout of the KB mirror manipulators, the alignment procedure as well as microfocus optimization results are presented.